2018
DOI: 10.22219/jes.v3i2.7579
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kausalitas Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia

Abstract: Human development is one of the indicators of the success of economic growth. The good quality of human resources goes hand in hand with economic growth, this is because resources as part of the factor of production are the most valuable assets in the economic activities of a country. This study aims to determine and analyze the causality of economic growth towards the quality of human resources. The method used in this study was using the Granger Causality method. Granger Causality Approach is used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…The results of this study are consistent with previous research by Umiyati et al (2017) and Arifin et al (2015) stated that economic growth has no significant effect to human development index. This study are not consistent the previous research Ady Soejoto et al (2015); Badrudin (2011); Adelfina and Jember (2016); Widani and Erawati (2016); Dewi and Sutrisna (2014); Syofya (2018); Wang et al (2018); Muslikhati (2018); Dewi (2017) and Lumbantoruan and Hidayat (2014) state that economic growth has a significant effect to human development index.…”
Section: Discussioncontrasting
confidence: 93%
“…The results of this study are consistent with previous research by Umiyati et al (2017) and Arifin et al (2015) stated that economic growth has no significant effect to human development index. This study are not consistent the previous research Ady Soejoto et al (2015); Badrudin (2011); Adelfina and Jember (2016); Widani and Erawati (2016); Dewi and Sutrisna (2014); Syofya (2018); Wang et al (2018); Muslikhati (2018); Dewi (2017) and Lumbantoruan and Hidayat (2014) state that economic growth has a significant effect to human development index.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings align with the results obtained by Sari et al, (2021), which demonstrate a similar one-way causality relationship between HDI and economic growth in Jambi Province. Furthermore, Muslikhati (2018) has reported a significant one-way relationship between HDI and economic growth, consistent with the research conducted by Fidelia (2020), who also found a one-way causality relationship between HDI and economic growth.…”
Section: Introductionsupporting
confidence: 88%
“…In this connection, reliable and quality human development is an important asset. (Muslikhati, 2018) Human development was first released by the United Nations Development Programme in 1996. According to the article, the improvement of human qualities becomes a process of expanding people's choices, described as a process that improves people's lives in many ways.…”
Section: Introductionmentioning
confidence: 99%